Determinants of non-adherence to antibiotic treatment guidelines in hospitalized adults with suspected community-acquired pneumonia: a prospective study - Dagfinn Lunde Markussen; Jannicke Slettli Wathne; Christian Ritz; Cornelis H. van Werkhoven; Sondre Serigstad; Rune Oskar Bjørneklett; Elling Ulvestad; Siri Tandberg Knoop; Synne Jenum; Harleen M. S. Grewal (Antimicrobial Resistance and Infection Control)
Abstract Background Antimicrobial resistance (AMR) is a global health threat with millions of deaths annually attributable to bacterial resistance. Effective antimicrobial stewardship programs are crucial for optimizing antibiotic use. This study aims to identify factors contributing to deviations from antibiotic treatment guidelines in hospitalized adults with suspected community-acquired pneumonia (CAP). Methods We conducted a prospective study at Haukeland University Hospital's Emergency Department in Bergen, Norway, from September 2020 to April 2023. Patients were selected from two cohorts, with data on clinical and microbiologic test results collected. We analysed adherence of antibiotic therapy to guidelines for the choice of empirical treatment and therapy duration using multivariate regression models to identify predictors of non-adherence. Results Of the 523 patients studied, 479 (91.6%) received empirical antibiotic therapy within 48 h of admission, with 382 (79.7%) adhering to guidelines. However, among the 341 patients included in the analysis of treatment duration adherence, only 69 (20.2%) received therapy durations that were consistent with guideline recommendations. Key predictors of longer-than-recommended therapy duration included a C-reactive protein (CRP) level exceeding 100 mg/L (RR 1.37, 95% CI 1.18–1.59) and a hospital stay longer than two days (RR 1.22, 95% CI 1.04–1.43). The primary factor contributing to extended antibiotic therapy duration was planned post-discharge treatment. No significant temporal trends in adherence to treatment duration guidelines were observed following the publication of the updated guidelines. Conclusion While adherence to guidelines for the choice of empirical antibiotic therapy was relatively high, adherence to guidelines for therapy duration was significantly lower, largely due to extended post-discharge antibiotic treatment. Our findings suggest that publishing updated guidelines alone is insufficient to change clinical practice. Targeted stewardship interventions, particularly those addressing discharge practices, are essential. Future research should compare adherence rates across institutions to identify factors contributing to higher adherence and develop standardized benchmarks for optimal antibiotic stewardship. Trial registration NCT04660084.